Stomach antral endocrine cells in patients with irritable bowel syndrome - EL-SALHY, MAGDY (D.A. Spandidos, 2014)
To the best of our knowledge, stomach antral endocrine cells have not previously been investigated in patients with irritable bowel syndrome (IBS). Thus, in the present study, 76 patients with IBS were examined (designated as IBS-total). Diarrhoea was the predominant symptom in 26 of these patients (IBS-D), while in 21 patients, the predominant symptoms were both diarrhoea and constipation (IBS-M) and in 29 patients the predominant symptom was constipation (IBS-C). Forty-three healthy subjects were enrolled as the controls. Stomach antral biopsy samples obtained from all of the subjects were immunostained using the avidin-biotin-complex method for serotonin, gastrin, somatostatin and serotonin transporter (SERT). The immunopositive cell densities and immunoreactivity intensities were determined by computer-aided image analysis. The density of the serotonin-immunoreactive cells was significantly decreased in the IBS-M patients and increased in the IBS-C patients relative to the controls. The immunoreactivity intensity did not differ significantly between the controls and IBS-total. The density of the gastrin-immunoreactive cells was significantly greater in the IBS-D, IBS-M and IBS-C patients than in the controls. The immunoreactivity intensity of gastrin was significantly greater in the IBS-D patients than in the controls. The density of the somatostatin-immunoreactive cells cells was significantly lower in the IBS-total, IBS-D, IBS-M and IBS-C patients than in the controls. The immunoreactivity intensities of both somatostatin and SERT did not differ significantly between the controls and IBS-total. The increase in gastrin cell density and the decrease in somatostatin cell density in all IBS subtypes may cause high levels of gastric secretion, which may in turn contribute to the high incidence of dyspepsia and gastro-oesophageal reflux observed in patients with IBS.